1991
DOI: 10.1086/132886
|View full text |Cite
|
Sign up to set email alerts
|

The effect of shock waves on the spectra of H II regions and planetary nebulae

Abstract: Emission lines from H II regions and planetary nebulae are contaminated by shock waves produced by stellar winds and supernova remnants. This effect is studied and it is found that it could be responsible for: (a) the difference between the O/H abundances derived from the O nebular lines coupled with H II region models and those derived from the observed I (4363)// (5007) ratio, (b) the large t 2 values observed in the Orion nebula and M 8, (c) the difference between the stellar and the H II region O/H abundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 35 publications
0
61
0
Order By: Relevance
“…Therefore, giant H ii regions in dwarf star-forming galaxies present the highest t 2 values. This may perhaps be related to their complex structure and dynamics due to the action of stellar winds and supernova remnants as it was firstly advocated by Peimbert et al (1991) or even the hardening of the energy distribution of ionizing photons as the central clusters evolve (Perez 1997). Although the simple Peimbert's formalism (Peimbert 1967) may be not completely adequate for such large temperature fluctuations, we consider it is still useful for parameterizing the problem until their existence and nature are definitely proven.…”
Section: Ionic Abundances and Abundance Discrepancymentioning
confidence: 93%
“…Therefore, giant H ii regions in dwarf star-forming galaxies present the highest t 2 values. This may perhaps be related to their complex structure and dynamics due to the action of stellar winds and supernova remnants as it was firstly advocated by Peimbert et al (1991) or even the hardening of the energy distribution of ionizing photons as the central clusters evolve (Perez 1997). Although the simple Peimbert's formalism (Peimbert 1967) may be not completely adequate for such large temperature fluctuations, we consider it is still useful for parameterizing the problem until their existence and nature are definitely proven.…”
Section: Ionic Abundances and Abundance Discrepancymentioning
confidence: 93%
“…Moreover, departures from a Maxwell-Boltzmann energy distribution of free electrons in nebulae in form of a "kappa-distribution" can mimic the effects of temperature fluctuations on the derived abundances (Nicholls et al 2012) and could explain their ultimate nature. Peimbert et al (1991) explored the effects of shock waves in the spectra of ionised nebulae. They showed that large temperature fluctuations may arise in the presence of shocks with velocities larger than 100 km s −1 .…”
Section: Abundance Discrepancy and Temperature Fluctuationsmentioning
confidence: 99%
“…It is also possible that the [O iii] λ4363 Å emission line is enhanced by shocks and the effect is likely to be stronger in regions with weaker lines (Peimbert et al 1991;Izotov et al 1997a). Consequently, this enhancement would result in the underestimation of the oxygen abundance.…”
Section: Electron Temperature and Electron Number Densitymentioning
confidence: 99%